2015
DOI: 10.3750/aip2015.45.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Selection and probiotic characterization of exoenzyme-producing bacteria isolated from the gut of Catla catla (Actinopterygii: Cypriniformes: Cyprinidae)

Abstract: . 2015. Selection and probiotic characterization of exoenzyme-producing bacteria isolated from the gut of Catla catla (Actinopterygii: Cypriniformes: Cyprinidae). Acta Ichthyol. Piscat. 45 (4): 373-384.Background. Exoenzyme-producing gut microbiota and their likely use as probionts have been widely investigated in major carps. However, reports on exoenzyme-producing capacity together with inhibition of fi sh pathogens are scarce. The presently reported study aimed at characterization of novel probionts from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 43 publications
1
4
0
1
Order By: Relevance
“…According to Ramesh et al 40 , the bile tolerance ability of probiotic candidate is an important characteristic, as it has to work in the gut environment (high bile concentration). Similar observations have also been reported by probiotic bacteria 19,39 . The evaluation of haemolytic activity is another important selection criterion of probiotic strain, as haemolytic bacteria may cause malfunction in the defence system 41,42 .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…According to Ramesh et al 40 , the bile tolerance ability of probiotic candidate is an important characteristic, as it has to work in the gut environment (high bile concentration). Similar observations have also been reported by probiotic bacteria 19,39 . The evaluation of haemolytic activity is another important selection criterion of probiotic strain, as haemolytic bacteria may cause malfunction in the defence system 41,42 .…”
Section: Resultssupporting
confidence: 79%
“…It has been suggested that enzyme-secreting GI tract bacteria play an important role in digestion of the host 38 . Therefore, from a nutritional point of view, probiotic bacteria gain special attention in aquaculture industries 39 . Table 4 presents the bile tolerance efficiency exhibited by the eight selected isolates.…”
Section: Resultsmentioning
confidence: 99%
“…La capacidad de aprovechar y degradar componentes como la chitina, es una característica muy útil para mejorar el proceso de digestión y asimilación en peces, a través de su microbiota asociada (Dutta et al, 2015). En el presente estudio, se logró identificar mediante proteómica la presencia de enzimas chitinasas de la cepa de B. amyloliquefaciens 11 CI-2.…”
Section: Discussionunclassified
“…Several investigations postulated host specificity of probiotics and suggested that putative probiotics should be isolated from the host species prior to use (Dutta et al . ; Mukherjee & Ghosh ; Li et al . ).…”
Section: Beneficial Role Of the Gut Microbiota: A Probiotic Approachmentioning
confidence: 99%
“…isolated from fish has rarely been evaluated (Dutta et al . ; Mukherjee & Ghosh ). Dietary supplementation of exogenous enzymes has been reported in several studies (Castillo & Gatlin ; Magalhães et al .…”
Section: Beneficial Role Of the Gut Microbiota: A Probiotic Approachmentioning
confidence: 99%